"Goths and Vandals" or "Civilized" Farmers? Common Lands and Agricultural Productivity in Early-Twentieth-Century Spain. Issue 2 (25th August 2015) - Beltrán Tapia, Francisco J.
Abstract : By analyzing the different factors affecting labor agricultural productivity in early-twentieth-century Spain, this article shows that common lands were not detrimental to agricultural development. Even though privatization fostered output per worker by bringing more land into cultivation, the role of the commons as provider of pasture and fertilizing materials counteracted that effect, especially in humid regions. The supposed advantages of dismantling the communal regime are thus not supported by the data.